Pengembangan Abon Lokan Berbasis Substitusi Jantung Pisang Kepok sebagai Pangan Lokal - Geri Geri; Lina Widawati; Hesti Nur’aini (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Lokan abon is a dry, fiber-like processed food product made from shredded lokan fruit that is seasoned, boiled, sliced, and fried. The substitution of kepok banana blossom in the processing of lokan abon is a food diversification technique based on local food in Bengkulu Province. This study aims to analyze the effect of adding kepok banana blossom on the quality of lokan abon and determine the best formulation. The study was conducted using an experimental method using a Completely Randomized Design with five levels of lokan meat and banana blossom composition, namely 100:0, 90:10, 80:20, 70:30, and 60:40. The parameters observed included yield, water content, protein content, fiber content, and organoleptic tests including color, taste, aroma, and texture. The results showed that the yield and water content of lokan abon ranged between 22.14% -22.14% and 6.92% 13.47%, respectively. The addition of banana blossoms increased fiber content (0.51% -1.08%) and decreased protein content. (15.30%-35.00%). The best treatment was obtained with a ratio of 80% lokan meat to 20% banana blossoms.